Tindak Tutur Tidak Langsung Literal dalam Drama ichi Rittoru No Namida - Devi Sucita, Ni Made; Yuliani Giri, Ni Luh Kade; Budiana, I Made (Humanis; Vol 20 No 1 (2017), 2017)
This research dealt withLiteral IndirectSpeech Act in Ichi Rittoru No Namida Drama by Masanori Murakami. The objective of research is to know theliteral indirect speech act which has an alteration on sentences function and sentences purpose. This research uses the speech act theory by Austin (1962) and literal indirect speech act theory by Parker (1986). The results of this research show that Ichi Rittoru No Namida Drama has three kinds speech wich has the alteration in sentence function such as the alteration from interogative sentence into declarative sentence, the alteration from declarative sentence into imperative sentence, and the alteration from interogative into imperative sentence. The purposes of using literal indirect speech act in Ichi Rittoru No Namida Drama consist of six function namely giving sugestion, giving command, giving advise,  giving refusel, notify, and giving complaint.